PEDAGOGICAL POSSIBILITIES OF COOPERATIVE FORMS ORGANIZATIONS OF THE EDUCATIONAL PROCESS IN HIGHER EDUCATION INSTITUTIONS - Nikulnikova, N.Ye. (Pedagogy of Higher and Secondary Education, 2008)
No abstract.